2004
DOI: 10.1007/s00421-004-1150-1
|View full text |Cite
|
Sign up to set email alerts
|

Muscle buffer capacity and aerobic fitness are associated with repeated-sprint ability in women

Abstract: In addition to a high aerobic fitness, the ability to buffer hydrogen ions (H+) may also be important for repeated-sprint ability (RSA). We therefore investigated the relationship between muscle buffer capacity (betamin vivo and betamin vitro) and RSA. Thirty-four untrained females [mean (SD): age 19 (1) years, maximum oxygen uptake (VO2peak) 42.3 (7.1) ml x kg(-1) x min(-1)] completed a graded exercise test (GXT), followed by a RSA cycle test (five 6-s sprints, every 30 s). Capillary blood was sampled during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
116
1
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(132 citation statements)
references
References 31 publications
8
116
1
7
Order By: Relevance
“…Sporiš et al, (2014) A manutenção dos níveis de potência após os sprints pode ser explicada pela capacidade de tamponamento da acidez muscular provocada pela presença elevada dos íons H+, considerada um importante atributo para a CSR (BISHOP; EDGE; GOODMAN, 2004). O aumento no IF é devido mudanças no meio intramuscular relacionado à falta de ATP disponível para o acoplamento entre actina e miosina e pela captação de cálcio pelo retículo sarcoplasmático; diminuição da concentração de glicogênio muscular levando ao aumento de amônia e produção de monofosfato de inosina, que está relacionado ao aumento de lactato muscular e ao decréscimo de fosfocreatina; diminuição do pH muscular que tem sido associado com a inibição da enzima fosfofrutoquinase e redução na glicólise e disfunções no processo de estímulo-contração (MOHR; KRUSTRUP; BANGSBO, 2005).…”
Section: Discussionunclassified
“…Sporiš et al, (2014) A manutenção dos níveis de potência após os sprints pode ser explicada pela capacidade de tamponamento da acidez muscular provocada pela presença elevada dos íons H+, considerada um importante atributo para a CSR (BISHOP; EDGE; GOODMAN, 2004). O aumento no IF é devido mudanças no meio intramuscular relacionado à falta de ATP disponível para o acoplamento entre actina e miosina e pela captação de cálcio pelo retículo sarcoplasmático; diminuição da concentração de glicogênio muscular levando ao aumento de amônia e produção de monofosfato de inosina, que está relacionado ao aumento de lactato muscular e ao decréscimo de fosfocreatina; diminuição do pH muscular que tem sido associado com a inibição da enzima fosfofrutoquinase e redução na glicólise e disfunções no processo de estímulo-contração (MOHR; KRUSTRUP; BANGSBO, 2005).…”
Section: Discussionunclassified
“…In the current soccer, the aerobic system plays an important role in the player's performance, being this energetic system the predominant in the energy supply in most part of the match 3,12 and it also enables fast recovery of the anaerobic systems after high-intensity exercises [2][3][4] . Thus, the aerobic capacity (anaerobic threshold), which corresponds to the highest exercise intensity which presents aerobic predominance and is identified by the highest intensity at which balance between lactate production and removal (maximal lactate steady state) occurs, plays an important role in the physical performance of soccer players.…”
Section: Discussionmentioning
confidence: 99%
“…Such fact evidences the increase in physical demand during the game and the importance of the aerobic resistance in the physical performance of the athlete. Aerobic fitness in soccer is responsible both for the energy supply in the endurance events, which are predominant in the game, and for the fast recovery after an anaerobic activity [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…Until the present moment, few studies have observed that the aerobic parameters such as ventilatory threshold 15 , VO 2 max 15,17,19 , MAV 11 , velocity in which the VO 2 max is reached (vVO 2 max) 13 , tau [19][20] were correlated with RS performance. However, the variables which signi cantly correlates are not always similar among studies, and thus, it is important to highlight that in the present study, as well as others, none aerobic variable correlated with the TT 10,12,16,[21][22]24 .…”
mentioning
confidence: 87%
“…However, there seems not to be a consensus regarding the importance of the anaerobic physiological aspects (i.e., cumulated oxygen de cit and blood lactate concentration at post-test) on RS performance, as others researches have demonstrated contradictory results 12,[15][16][17] . In addition to anaerobic parameters, G et al 18 highlighted that the aerobic parameters might in uence the RS performance, insofar as, performing several RS with incomplete recovery increases the energy transfer by the oxidative metabolism.…”
Section: Introductionmentioning
confidence: 99%